EXPLORING THE INFLUENCE OF ARTIFICIAL INTELLIGENCE ON THE GOVERNANCE OF POLITICAL CULTURE: PERSPECTIVES FROM ALGERIAN YOUTH - Ahmed , Dr. Chikhaoui (The journal of contemporary issues in business and government, 2024)
This study investigates the impact of modern technology and artificial intelligence on the political culture among Algerian youth. The aim is to explore the evolving political views, democratic aspirations, and cultural values influenced by technological advancements. Conducted with 650 participants from Dr. Tahar Moulay University, the research utilizes a questionnaire to extract valuable insights. The results indicate that the pervasive use of artificial intelligence and modern technology plays a pivotal role in shaping and reinforcing democratic aspirations among Algerian youth. This reflects a transformative journey beyond conventional Western paradigms, marked by a desire for political freedom, active civic participation, and a decisive rejection of traditional norms.